Effects of Loaded Plyometric Exercise on Post-Activation Performance Enhancement of Countermovement Jump in Sedentary Men - Souza, Victor Alvino [UNESP]; Barreto, Renan Vieira [UNESP]; Mantovani, Guilherme Beneduzzi [UNESP]; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sérgio [UNESP]; Nosaka, Kazunori; Lima, Leonardo Coelho Rabello [UNESP] (Taylor & Francis, 2022)
Purpose: Explosive performance is increased right after performing loaded resistance exercise, which is known as post-activation performance enhancement (PAPE). Method: We investigated the effects of a plyometric exercise (PLYO) consisting of five sets of six drop-jumps from a 52-cm platform with a load corresponding to 20% body mass on changes in countermovement jump (CMJ) height in sedentary young men. Eleven young nonresistance trained men (19.6 ± 1.8 y, 69 ± 9 kg, 1.76 ± 0.08 m) who showed more than 4% increase in CMJ height at 4 min after five back squats with five-repetition maximum load participated in the study. Their responses to the back squat exercise were examined before (baseline) and 15 minutes, 24 and 48 hours post-PLYO. Exercise-induced muscle damage markers (maximal voluntary contraction torque [MVC], and quadriceps muscle soreness) were assessed at baseline, 15 minutes, 24 and 48 hours following PLYO. Results: MVC torque decreased (p < .05) at 15 minutes post-PLYO (−15.1 ± 9.7%) but returned to the baseline at 24 hours post-PLYO. Muscle soreness developed (p < .05) at 48 hours (21.0 ± 20.3 mm) after PLYO, indicating minor muscle damage. CMJ height increased (p < .05) after the five squats at baseline (7.6 ± 3.8%) indicating PAPE, but no such increase was found at 15 minutes, 24 and 48 hours after PLYO. However, CMJ height before the squat exercise was greater (p < .05) at 24 (5.9 ± 7.0%) and 48 hours post-PLYO (9.1 ± 8.5%) than the baseline. Conclusions: These results showed that PAPE disappeared after PLYO that induced minor muscle damage, but CMJ height increased at 24–48 hours in the recovery from PLYO exhibiting a priming effect.
Keywords: Countermovement jump; delayed onset muscle soreness; drop jump; jump height